New eriophyoid mites (Acari: Eriophyoidea) associated with grasses from Mongolia - Skoracka, Anna; Shi, Aoxiang; Pacyna, Anna (Zootaxa, 2001)
Two new species, Aculodes mongolicus sp. n. from Hordeum brevisubulatum (Trin.) Link, Eriophyes bromusi sp. n. from Bromus inermis Leyss, are described from Mongolia. Four new records of eriophyoid mites collected from grasses in Mongolia are also presented.